The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1124/jpet.106.111443
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-Independent, Inhibitory Effects of Cyclic Adenosine 5′-Monophosphate on Ca2+ Regulation of Phosphoinositide 3-Kinase C2α, Rho, and Myosin Phosphatase in Vascular Smooth Muscle

Abstract: We have recently demonstrated in vascular smooth muscle (VSM) that membrane depolarization by high KCl induces Ca 2ϩ -dependent Rho activation and myosin phosphatase (MLCP) inhibition (Ca 2ϩ -induced Ca 2ϩ -sensitization) through the mechanisms involving phosphorylation of myosin-targeting protein 1 (MYPT1) and 17-kDa protein kinase C (PKC)-potentiated inhibitory protein of PP1 . In the present study, we investigated whether and how cAMP affected Ca 2ϩ -dependent MLCP inhibition by examining the effects of for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 40 publications
(73 reference statements)
4
37
0
Order By: Relevance
“…11,22 We tested the effects of WMN infusion on blood pressure and vascular activities of PI3K-C2␣, Rho, and MLCP in SHRs. WMN substantially lowered systolic blood pressure with the maximal decline of Ϸ70 mm Hg at 10 minutes after infusion in 12-week-old SHRs ( Figure 5A).…”
Section: Wortmannin Lowers Systolic Blood Pressure the Activities Ofmentioning
confidence: 99%
“…11,22 We tested the effects of WMN infusion on blood pressure and vascular activities of PI3K-C2␣, Rho, and MLCP in SHRs. WMN substantially lowered systolic blood pressure with the maximal decline of Ϸ70 mm Hg at 10 minutes after infusion in 12-week-old SHRs ( Figure 5A).…”
Section: Wortmannin Lowers Systolic Blood Pressure the Activities Ofmentioning
confidence: 99%
“…2). The agonist-induced phosphorylation of CPI-17 has been shown to be inhibited by either RhoK inhibitors or PKC inhibitors, depending on the type of agonist and the vascular tissues (22,29,30). Furthermore, the contribution of RhoK and PKC to the CPI-17 phosphorylation differed with the phase of contraction, i.e., early vs late phase (9).…”
Section: +mentioning
confidence: 99%
“…The key component of generating and sustaining vascular tone is the phosphorylation state of the smooth muscle contractile apparatus myosin light chain (MLC) (34). It has been reported that cAMP decreases MLC phosphorylation by activating the MLC phosphatase (MLCP) (3,4); however, to the best of our knowledge, a potential link between estrogen, cAMP, and MLC has not been investigated. In this study described here, we tested the hypothesis that GPER activation induces coronary relaxation by activating MLCP via cAMP/PKA signaling.…”
mentioning
confidence: 99%